Modified Biochar From Waste Biomass (Palm Oil Sludge) To Treat Dye Wastewater - Nur Ain Jannah, Mohd Zain (2023)
Currently, one of the biggest issues affecting the entire world is water pollution brought on by textile manufacturers' inability to properly dispose of their wastewater. Due to the textile industry's large-scale production of brightly coloured wastewater carrying a wide variety of persistent contaminants, wastewater including dyes is a serious polluter of the environment that also negatively impacts human health. Palm oil sludge (POS) is a liquid waste product that can be recovered as low-quality oil. The wastes by the palm oil industry are divided into two categories: solid waste and liquid waste. The palm oil sludge has a bad odour and leads to land and water pollution which indirectly creates hygienic and environmental issues. The expensive and complex types of filtration system in the market make it hard for people to have the good quality of water filter. The idea is to make a low-cost filter by using biomass as a raw material for biochar filter. The biochar undergoes pyrolysis at 3 difference temperature, that is 250C, 300C, 400C and then impregnated in phosphoric acid with 2:1 for chemical. The result is taken and collected. The parameter collected from the data are Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid and Colour Admi. Result shown that the temperature effect the result. The best result for all parameter is COD is 61.3%, BOD is 5.13%, TSS is 63.3% and lastly for Colour Admi is 56.75%. Lastly, the temperature at which biochar is produced through pyrolysis can have an impact on its efficiency for treatment of wastewater. This is because the temperature can affect the physical and chemical properties of the biochar, such as its surface area, pore structure, and chemical composition, which can impact its ability to adsorb pollutants from wastewater.